THE MAKING OF PROFILE BOOK OF TOURISM OBJECTS IN NORTH RUPAT - Robita Robita; Muhammad Sabri (Politeknik Negeri Bengkalis, 2016)
Abstract : Rupat Island, part of Bengkalis Regency of Riau Province has many interesting tourism objects and attractions. For many years, North Rupat has become tourism destination for tourists, especially the domestic tourists. Lack of creative promotion makes North Rupat known only by the domestic tourists. Therefore, creative promotional items such as a profile book which is written in English is needed to promote North Rupat to international tourists. This study is about making a profile book about tourism objects and attractions in North Rupat. The profile book is made by using Photoshop CS3 program. It describes some of tourism objects including Natural Tourism, Cultural Tourism and Man-made Tourism. The profile book consists of eighteen pages with pictures and description text in dual language; English and Bahasa. The profile book is expected to be able to help the government of Bengkalis Regency to promote the tourism objects in North Rupat both for domestic and international tourists.Â Keywords: Tourism Object, Profile Book